Research on User Experience during Interactions with Mobile Applications for Diabetics - Przemysław Bajda; Rafał Baliński; Mariusz Dzieńkowski (Journal of Computer Sciences Institute)
The purpose of this study was to assess the influence of the appearance and structure of the application interface on task completion speed and user experience. Two data collection methods were used in the study: eye tracking and the System Usability Scale (SUS) questionnaire. Eye tracking provided information on eye movement and fixation while using the application, while the SUS questionnaire helped evaluate the overall usability level and user satisfaction. Three applications were examined (mySugr, Diabetes diary control from Google Play, and one proprietary application implemented for the purposes of the study. It was found that the proprietary SugarCare application characterized by a simple, modern, and readable interface achieved the highest results in terms of task completion times and SUS questionnaire scores. The mySugr application, which also has a clear and simple interface, took the second place. The Diabetes diary control application performed the worst, as it had a complex and less user-friendly interface. On the basis of the obtained results, mobile applications for diabetics with a clear interface proved to accelerate the task completion process and have a positive impact on user experience. These conclusions stem from the analyses of the metrics used indicating the benefits resulting from accessibility of simple and intuitive application interfaces in terms of efficacy and user satisfaction.